Mechanism of Inactivation of Transforming Deoxyribonucleic Acid by X Rays - Randolph, M. L. (1971)
Transforming deoxyribonucleic acid (DNA) from Haemophilus influenzae was exposed to X rays either in phosphate buffer or in 10% yeast extract. Relations between determinations of biological inactivation, DNA uptake by competent H. influenzae, integration of DNA into the competent cell genome, and induced single-and double-strand breaks indicate that transforming DNA is inactivated by the direct and the indirect effect of X radiation primarily because integration of DNA is prevented as a result of the production of double-strand breaks.